The Impact of Ecological Sustainability on Tourists’ Satisfaction and Revisit Intention: A Case Study in Langkawi, Malaysia - Shamim, Nik Mohamad; Ismail, An Nur Nabila; Rosely, Nurhidayah; Thani, Ayu Kamareenna Abdullah (Advances in Social Sciences Research Journal, 2024)
More concerns regarding the environmental impact are observed as the global travel industry continues to expand. The present study examined the correlation between ecological sustainability, tourists’ satisfaction, and the tendency to revisit past destinations to understand the impact of tourists’ perceptions regarding the environmental practices in travel destinations on overall satisfaction and subsequent revisit intention. A total of 200 local and international tourists participated in this study. The data collection process was conducted via self-administered questionnaires distributed in Langkawi, Malaysia. The results indicated a significant positive association between ecological sustainability and tourists’ overall satisfaction with respective trip experiences. A positive correlation also existed between tourists’ perception of travel destinations actively engaging in ecological sustainability practices and the reported satisfaction levels. Moreover, this increased satisfaction level positively impacted tourists’ intention to revisit the same destination in the future. The findings provided significant implications with high relevance to both destination planners and policymakers. Implementing and promoting effective ecological sustainability practices could not only enhance the attractiveness of travel destinations but also sustain high loyalty among tourists.